2010
DOI: 10.1590/s0303-76572010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Programa de reabilitação de trabalhadores com LER/DORT do Cesat/Bahia: ativador de mudanças na saúde do trabalhador

Abstract: Este artigo apresenta a concepção e a implantação do Programa de Retorno ao Trabalho (PRT), em fase de projeto piloto, como parte do Programa de Reabilitação de Trabalhadores com LER/DORT do Cesat/Bahia, desde 2007. Esta experiência tem-se apresentado como um processo ativador de diálogos e mudanças no campo da saúde do trabalhador no estado da Bahia, envolvendo os diversos atores implicados na reabilitação de trabalhadores. É apresentado o GT de Reabilitação/Cesat, sua constituição, composição e característic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
21

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 11 publications
0
18
0
21
Order By: Relevance
“…By segmenting these results according to the health field, the use of the ICF has the following division into Brazilian research: neurology, observed in 16 publications 11,16,18,21,23,34,35,38,39,[46][47][48][49][50][51]54 ; orthopaedics, in 12 publications 15,19,22,24,25,27,28,30,32,41,42,45 ; health surveillance, in two 36,43 ; HIV, in two 29,55 ; women's health 40 , endocrinology 31 , hearing and visual deficiencies 10 , gerontology 37 and public health 52 , in one publication each.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By segmenting these results according to the health field, the use of the ICF has the following division into Brazilian research: neurology, observed in 16 publications 11,16,18,21,23,34,35,38,39,[46][47][48][49][50][51]54 ; orthopaedics, in 12 publications 15,19,22,24,25,27,28,30,32,41,42,45 ; health surveillance, in two 36,43 ; HIV, in two 29,55 ; women's health 40 , endocrinology 31 , hearing and visual deficiencies 10 , gerontology 37 and public health 52 , in one publication each.…”
Section: Resultsmentioning
confidence: 99%
“…The educational institution that has appeared most frequently in national periodical publications was the Universidade de São Paulo (USP), with 11 publications 1,14,[18][19][20]25,28,29,33,41,44 , followed by the Universidade Federal de Minas Gerais (UFMG), with seven 12,13,15,17,22,30,38 , and the Universidade Federal da Bahia (UFBA), with three 27,32,42 and the Universidade Federal do Rio de Janeiro (UFRJ), with two 31,34 . There are another 25 institutions that appear with one publication each [10][11][12][15][16][17][18]21,23,24,26,[35][36][37][38][39][40]42,43 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A reabilitação profissional é de extrema importância quando se fala sobre saúde do trabalhador e principalmente nos casos dos Distúrbios Osteomusculares Relacionados ao Trabalho (DORT), tendo em vista o alto índice de afastamento para tratamento (Lima et al, 2010). A reabilitação do funcionário deve ser um conjunto integrado de ações com a finalidade de resgatar as capacidades física, psicológica e social quando estes são acometidos por agravos de saúde, que resultam na incapacidade para o trabalho (Takahashi et al, 2010).…”
Section: Introductionunclassified